2020
DOI: 10.1080/02723646.2020.1738980
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of salt-affected soil amended by leonardite

Abstract: Salt-affected soils are widely distributed in arable croplands worldwide with potential productivity so that it is important to develop and utilize these soils. This study investigated the effects of leonardite at the application dosage of 0 (CK), 1% (T1), 3% (T2), and 5% (T3) on amending salt-affected soils under intermittent leaching. Results showed that leaching effectively reduced the electrical conductivity (EC) in soil at CK/T1/T2/T3 with 67.4%/70.9%/75.7%/ 75.6% of salt discharged. As the dominant catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Because humic acids along with fulvic acids are essential components of soil organic matter, playing a critical role in improving soil properties [26], it is expected that the use of leonardite directly and leonardite-derived humic substances as soil amendments and plant stimulants will improve the physicochemical and biological aspects of soil, promoting plant yield and quality [25,27,28]. Despite the above, previous research has focused on identifying and evaluating the effects of leonardite on soil trace element mobility [29][30][31][32], soil microbiome structure and functionality [24,28,30], stability of soil aggregates [33], as well as crop tolerance to soil drought [23] and salinity [34]. However, less research has been performed on how this organic material affects grapevine nutrition and harvest 5uality.…”
Section: Introductionmentioning
confidence: 99%
“…Because humic acids along with fulvic acids are essential components of soil organic matter, playing a critical role in improving soil properties [26], it is expected that the use of leonardite directly and leonardite-derived humic substances as soil amendments and plant stimulants will improve the physicochemical and biological aspects of soil, promoting plant yield and quality [25,27,28]. Despite the above, previous research has focused on identifying and evaluating the effects of leonardite on soil trace element mobility [29][30][31][32], soil microbiome structure and functionality [24,28,30], stability of soil aggregates [33], as well as crop tolerance to soil drought [23] and salinity [34]. However, less research has been performed on how this organic material affects grapevine nutrition and harvest 5uality.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kiyas (2020), the use of leonardite in bean plants in a salty environment increased both its growth and ion uptake. Wang et al (2020) determined that the evacuated salt increased and the EC value decreased in parallel with the increase in the leonardite dose. Kaya et al (2020) reported that sulphur-enriched leonardite and humic acid materials could be used to preserve the yield of maize crops.…”
Section: Discussionmentioning
confidence: 99%